Reanime: simulador de realidade virtual para avaliação de treinamento em reanimação neonatal - Oliveira, Ana Carolina Costa de (2020)
Considering that the birth of a child presents the greatest physiological transition in human life, however, given the various extra uterine adaptations, neonatal resuscitation is necessary in neonatal care because of the demand for cognitive, technical and behavioral skills, which require knowledge, assimilation of findings and decision making. Therefore, training becomes an essential element in the clinical training of health professionals in the process of neonatal resuscitation. It is known that teaching in the health area focuses on theoretical learning, which is usually accompanied by clinical experience through direct contact with the patient. Given this reality, studies appear using virtual reality for health training with the proposal of improving the quality of teaching, promoting professional safety, minimizing costs and resources used. However, when the training is not successful, it is not able to generate feedback on the users' performance. Therefore, the objective of this research is to develop a virtual reality simulator for evaluating the training of health professionals in neonatal resuscitation. This is an experimental research of a qualitative and quantitative nature by non-probabilistic sampling for convenience. Initially, a systematic review of the academic literature in the field of health was carried out, followed by a mapping of the steps, adapted and appropriate, according to the environment of virtual reality and based on its technological limitations of the neonatal resuscitation process for health professionals. Then the REANIME simulator was built for this propose, Unity was used for the development, Blender, Cheetah 3D, Photoshop to create interactive 3D content and, for the integration of the immersion devices, the Uduino. For the construction of the evaluation model for training, statistical analysis was used, the expert fuzzy system based on rules, decision map, which resulted in the decision model. In addition, a descriptive and interpretative analysis of the data was performed, after the use of REANIME by health professionals and, finally, the analysis of Cronbach's alpha to identify the internal consistency of the instrument in general and by activities. Thus, it can be observed that REANIME is an innovative tool for evaluating the training of health professionals based on neonatal resuscitation, according to the Neonatal Resuscitation Program of the Brazilian Society of Pediatrics for newborns over 34 weeks of gestation. Regarding to the collected results, using the simulator integrated with the immersion devices, it can be said that it helps the teaching-learning process, because through technology users interact with the simulated environment, making it viable to training in difficult to access places and with the advantage of being low cost. It is concluded that the results were satisfactory for the validation of linguistic variables, based on the use of the fuzzy specialist system, the technology in tele-education and the feasibility for the learning of health professionals. Therefore, REANIME is a virtual reality simulator with Cronbach's alpha of 94.3% for internal consistency of all neonatal resuscitation activities, which makes it reliable for the training carried out, through simulation, for the training of health professionals.